A one-pot, three-component reaction for the synthesis of novel 7-arylbenzo[c]acridine-5,6-diones - Khullar, S.; Mandal, S.K. (Royal Society of Chemistry, 2014)
A one pot domino protocol for an efficient synthesis of 7-arylbenzo[c]acridine-5,6-diones, with a novel nucleus, has been developed by reacting 2-hydroxynaphthalene-1,4-dione, aromatic aldehydes and aromatic amines using environmentally benevolent p-toluene sulphonic acid as a catalyst. An exciting feature of this communication is the reaction mechanism that depends on the reaction solvent.
Only IISERM authors are available in the record.
Keywords: 5,6-diones; Hydroxynaphthalene; p-toluene sulphonic acid